BIRTH AND DEPLOYMENT OF THE STATE FOLLOWING THE WESTPHALIA MODEL (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This article tackles the birth of modern State after the end of the Thirty Years’ War, following Schmitt and Foucault’s political thinking. Specifically, the theory of large spaces, but mostly the theory of governmentality by the French philosopher, with its special attention to biopower and the police, allows us to shed light on the main characteristics of the form State that emerged after Westphalia.